Las sirvientas en Pamplona, según el censo de 1900 - Cía García, María Victoria (Huarte de San Juan. Geografía e Historia, 1998)
The aim of the present study is trying to be a contribution to the knowledge about the work of women during the Industrial Revolution and the changes attached to the appearance of a new mentality. These changes are perfectly shown thanks to the information obtained about the domestic service in Pamplona in 1900.